De novo nonsense mutations in ASXL1 cause Bohring-Opitz syndrome - Hoischen, Alexander; van Bon, Bregje W M; Rodríguez-Santiago, Benjamín; Gilissen, Christian; Vissers, Lisenka E L M; de Vries, Petra; Janssen, Irene; van Lier, Bart; Hastings, Rob; Smithson, Sarah F; Newbury-Ecob, Ruth; Kjaergaard, Susanne; et al. (Nature genetics, 2011)
Han Brunner and colleagues report the identification of de novo nonsense mutations in ASXL1 in individuals with Bohring-Opitz syndrome, which is characterized by intellectual disability, distinctive facial features and multiple congenital malformations. Bohring-Opitz syndrome is characterized by severe intellectual disability, distinctive facial features and multiple congenital malformations. We sequenced the exomes of three individuals with Bohring-Opitz syndrome and in each identified heterozygous de novo nonsense mutations in ASXL1 , which is required for maintenance of both activation and silencing of Hox genes. In total, 7 out of 13 subjects with a Bohring-Opitz phenotype had de novo ASXL1 mutations, suggesting that the syndrome is genetically heterogeneous.